Recent Advances in Improving the Stability of Perovskite Solar Cells - Tiep, Nguyen Huy (2016)
Organometal trihalide perovskite have recently emerged as promising materials for low-cost, high-efficiency solar cells. In less than five years, the efficiency of perovskite solar cells (PSC) has been updated rapidly as a result of new strategies that are adopted in its fabrication process, including device structure, interfacial engineering, chemical compositional tuning, and the crystallization kinetics control. Up to now, the champion efficiency of PSC has reached 20.1%, which is close to that of single crystal silicon solar cells. However, the stability of PSC devices is still unsatisfactory and becomes the main bottleneck that impedes their commercialization. Here, we summarize the recent study on the degradation mechanisms of organometal trihalide perovskites in PSC devices and the strategies for stability improvement.